2020
DOI: 10.1289/ehp6012
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Drinking Water Chlorination by-Products and Fetal Growth and Prematurity: A Nationwide Register-Based Prospective Study

Abstract: BACKGROUND: Chlorination is globally used to produce of safe drinking water. Chlorination by-products are easily formed, and there are indications that these are associated with adverse reproductive outcomes. OBJECTIVES: We conducted a nationwide register-based prospective study to assess whether gestational exposure to the four most common chlorination by-products [total trihalomethanes (TTHMs)] via tap water was associated with risk of small for gestational age (SGA), preterm delivery, and very preterm deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Animal studies have shown that some DBPs can pass through the placenta, which can lead to intrauterine growth retardation, decreased birth length and weight, and increased birth defects in rodent species. , Previous epidemiological studies also reported associations between gestational exposure to DBPs and fetal anthropometric measures at delivery, such as birth weight and birth length, as well as adverse birth outcomes [e.g., small for gestational age (SGA) and preterm birth]. However, evidence linking DBP exposure to intrauterine growth is sparse. Repeated ultrasound measures reflect the changing rate of growth in utero and capture specific fetal growth measures such as abdominal circumference (AC), biparietal diameter (BPD), and femur length (FL), which facilitates an investigation of the effects of DBP exposure on specific anthropometric parameters during different gestational periods.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that some DBPs can pass through the placenta, which can lead to intrauterine growth retardation, decreased birth length and weight, and increased birth defects in rodent species. , Previous epidemiological studies also reported associations between gestational exposure to DBPs and fetal anthropometric measures at delivery, such as birth weight and birth length, as well as adverse birth outcomes [e.g., small for gestational age (SGA) and preterm birth]. However, evidence linking DBP exposure to intrauterine growth is sparse. Repeated ultrasound measures reflect the changing rate of growth in utero and capture specific fetal growth measures such as abdominal circumference (AC), biparietal diameter (BPD), and femur length (FL), which facilitates an investigation of the effects of DBP exposure on specific anthropometric parameters during different gestational periods.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 83 localities remained as our study area ( Figure 1 ). We used a similar study design as in a study assessing TTHM exposure in relation to small for gestational age and preterm delivery ( Säve-Söderbergh et al. 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…We estimated a trimester-specific 3-month average TTHM exposure for each individual pregnancy by using a locality-specific and multiannual monthly average of TTHM [as outlined by Säve-Söderbergh et al. ( 2020 )]. Briefly, by using a multiannual average for each month and locality for assigning the exposure, we a ) accounted for seasonal variations ( Andersson et al.…”
Section: Methodsmentioning
confidence: 99%
“…Dibromoacetic acid and bromodichloromethane can pass through amniotic fluid, placentas, fetuses (rats and rabbits), or milk (rats) (Christian et al, 2001). Thus, these compounds have induced pregnancy loss (Narotsky et al, 2011), adverse pregnancy outcomes (APO) like short gestational age and stillbirth (Bonou, Levallois, Giguère, Rodriguez, & Bureau, 2017; Cao et al, 2016; Mashau, Ncube, & Voyi, 2018; Save‐Soderbergh, Toljander, Donat‐Vargas, Berglund, & Åkesson, 2020; Summerhayes et al, 2021), congenital central nervous system anomalies (Hwang & Jaakkola, 2003), skeletal defects (Stankevič et al, 2020), pre‐term delivery (King, Dodds, & Allen, 2000). Pregnant women who drank more than five glasses of water with DBP concentrations of about 75 μg/L each day displayed a significant relationship between APO and DBP and most exhibited intrauterine growth retardation (Wright, Schwartz, & Dockery, 2004).…”
Section: Introductionmentioning
confidence: 99%